Existential Reflections on Counselling - Peavy, Vance (Canadian Journal of Counselling and Psychotherapy, 2012)
The main contention in this article is that philosophy, especially as it is lived, is indispensable to counsellors, as well as to clients, in their search for ever more efficacious life situations. How can the counsellor be of service to others in the formation of their life projects if the counsellor himself has no substantial ideas of his own on the subject of how to live? This question is examined from an existential perspective including a commentary on a case example from the author's own counselling practice.